2014
DOI: 10.1590/s0100-67622014000100008
|View full text |Cite
|
Sign up to set email alerts
|

Carbon sequestration and nutrient reserves under differen t land use systems

Abstract: -This study evaluated the contribution of agroforestry (AFS) and traditional systems to carbon sequestration and nutrient reserves in plants, litter and soil. The study was carried out in the semiarid region of Brazil in a long-term experiment on an experimental farm of the goat and sheep section of the Brazilian Agricultural Research Corporation (Embrapa). Two agroforestry systems were investigated: agrosilvopastoral (ASP) and forest-pasture areas (SP) as well as traditional agriculture management (TM), two a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 31 publications
(38 reference statements)
0
15
1
2
Order By: Relevance
“…), values which are lower than those obtained by Aguiar et al (2014) in a study evaluating an area of dry forest in Brazil preserved for over 50 years, where they found 67.3 t C ha -1 . Dry forests can stock around 20 to 150 t C ha -1 (TIESSEN et al, 1998).…”
Section: Stocks Of Carbon In the Woody Componentcontrasting
confidence: 60%
“…), values which are lower than those obtained by Aguiar et al (2014) in a study evaluating an area of dry forest in Brazil preserved for over 50 years, where they found 67.3 t C ha -1 . Dry forests can stock around 20 to 150 t C ha -1 (TIESSEN et al, 1998).…”
Section: Stocks Of Carbon In the Woody Componentcontrasting
confidence: 60%
“…The annual mean temperature is 28°C, and the mean total annual precipitation is 759 mm. The soils of the studied areas were a typical Arctic Cromic Luvisol and typical Arctic Hipocromic Luvisol, with a clayey texture (AGUIAR et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…The stability of this biome over time is based on the energy flow and nutrient cycling, as well as on the regulation of the population of animals and plants (AGUIAR et al, 2014). In 2002, the "Center for Vegetable Information of the Northeast" (CNIP), concluded that 40% of the species found in the Caatinga were from the Fabaceae family, with the majority of these species having the capacity to fix N2 (Santos et al, 2010), amongst them Freitas et al (2010) stressed that in environments natural regeneration, fixation can reach 130 kg N ha -1 year -1 .…”
Section: Degradation and Importance Of The Caatinga's Woody Stratum Tmentioning
confidence: 99%